2017
DOI: 10.1590/1678-4685-gmb-2016-0123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BCHE single nucleotide polymorphisms on lipid metabolism markers in women

Abstract: Butyrylcholinesterase (BChE) activity and polymorphisms in its encoding gene had previously been associated with metabolic traits of obesity. This study investigated the association of three single nucleotide polymorphisms (SNPs) in the BCHE gene: -116G > A (rs1126680), 1615GA (rs1803274), 1914A < G (rs3495), with obesity and lipid metabolism markers, body mass index (BMI), total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), triglyceride (TG) level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, BChE is a protein synthesized in the liver and abundant in plasma, which hydrolyses acetylcholine. Although very similar to its sister protein, acetylcholinesterase, biological functions of BChE appear to be more varied but less understood 18 . In a recent study in China, low circulating BChE was found to be highly associated with HIV severity, was predictive of mortality in adults, and was proposed as a plausible strategy for severity classification among adults with HIV 19 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, BChE is a protein synthesized in the liver and abundant in plasma, which hydrolyses acetylcholine. Although very similar to its sister protein, acetylcholinesterase, biological functions of BChE appear to be more varied but less understood 18 . In a recent study in China, low circulating BChE was found to be highly associated with HIV severity, was predictive of mortality in adults, and was proposed as a plausible strategy for severity classification among adults with HIV 19 .…”
Section: Discussionmentioning
confidence: 99%